요골 간부 골절 치료 후 지연 발견된 원위 척골의 전방 탈구 - 전숙하(Suk Ha Jeon); 이상림(Sanglim Lee) (The journal of the Korean Orthopaedic Association, 2021)
원위 요척 관절의 전방 탈구 치료가 지연된 경우에는 수근부 통증과 전완의 회전 운동의 제한이 동반되어 결국 구제술이 필요한퇴행성 관절염이 발생할 수 있다. 24세 남자가 요골 간부 골절 수술 후 통증과 회전 운동 제한으로 내원하였다. 금속판으로 고정된요골의 간부에서 7도의 전방 각형성이 관찰되었으며 척골 두가 전방으로 탈구되어 회외전에서 결손부가 요골의 S자 절흔 전방 경계에 걸려 탈구가 지속되는 소견이 관찰되었다. 부정 유합된 요골의 교정의 절골술과 척골 두 골결손 근위부의 골을 원위 결손 부위로 이동시키는 절골술을 시행하여 원위 요척 관절이 전완의 회전에 안정적으로 정복이 유지되도록 하였다. 수술 후1 9개월에 전완 회전 운동 범위와 통증이 개선된 것을 확인하였다. Delayed treatment of volar dislocation of the distal radioulnar joint can result in wrist pain, limited rotation of the forearm, and degenerative arthritis that could be managed only by salvage procedures. A 24-year-old male patient presented with wrist pain and a loss of forearm rotation after surgery for a radial shaft fracture. The shaft of the radius was fixed with a plate and screws with a volar angulation of 7°. The ulnar head was dislocated volar to the distal radius, and the bone defect in the ulnar head was impacted into the volar rim of the sigmoid notch of the radius, preventing the head from being reduced in the joint. Corrective osteotomy of the malunited radial shaft and sliding osteotomy of the proximal ulnar head were performed to fill the distal bone defect. Pain and range of the forearm rotation were improved at postoperative 19 months. KCI Citation Count: 0